The transcriptomic response of Hyphantria cunea (Drury) to the infection of Serratia marcescens Bizio based on full-length SMRT transcriptome sequencing - Zhang, Ling; Tang, Xinyi; Wang, Zhiqiang; Tang, Fang (Frontiers in Cellular and Infection Microbiology, 2023)
Hyphantria cunea Drury is a globally important forest pest. We found that the Serratia marcescens Bizio strain SM1 had insecticidal activity against H. cunea, but the transcriptomic response of H. cunea to SM1 were not clear. Therefore, we performed full-length sequencing of the transcriptomes of H. cunea larvae infected with SM1 and the control group. A total of 1,183 differentially expressed genes (DEGs) were identified by comparing the group infected with SM1 and the control group, including 554 downregulated genes and 629 upregulated genes. We found many downregulated genes in metabolic pathways. Furthermore, some of these downregulated genes were involved in cellular immunity, melanization, and detoxification enzymes, which showed that SM1 weakened H. cunea immunity. In addition, genes in the juvenile hormone synthesis pathway were upregulated, which was detrimental to the survival of H. cunea. This research analyzed the transcriptomic response of H. cunea to SM1 by high-throughput full-length transcriptome analysis. The results provide useful information to explore the relationship between S. marcescens and H. cunea, and theoretical support for the application of S. marcescens and the control of H. cunea in the future.